2015
DOI: 10.1515/eletel-2015-0042
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Feed Forward Neural Network-based Model for Air Pollutants Evaluation of Single Monitoring Stations in Urban Areas

Abstract: Abstract-In this paper, air pollutants concentrations for N O2, N O, N Ox and P M 10 in a single monitoring station are predicted using the data coming from other different monitoring stations located nearby. A cascade feed forward neural network based modeling is proposed. The main aim is to provide a methodology leading to the introduction of virtual monitoring station points consistent with the actual stations located in the city of Catania in Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In this regards, the use of machine learning techniques, which are increasingly being developed in a wide variety of areas [30][31][32][33][34] including the field of hearing [35], would allow us the extraction of additional information with respect to the mere count of occurrences from the spike patterns, leading us to an improvement of the detection performances. Hereof, since today's machine learning systems are frequently based on neural networks [36][37][38][39][40] (among which the SNNs [41]) a direction could be that of using nature-inspired recognition systems, which would allow us to better mimic the subsequent stages of PAS (i.e., SNC part of fig. 1) and to expand the system to model the complete HAS.…”
Section: Discussionmentioning
confidence: 99%
“…In this regards, the use of machine learning techniques, which are increasingly being developed in a wide variety of areas [30][31][32][33][34] including the field of hearing [35], would allow us the extraction of additional information with respect to the mere count of occurrences from the spike patterns, leading us to an improvement of the detection performances. Hereof, since today's machine learning systems are frequently based on neural networks [36][37][38][39][40] (among which the SNNs [41]) a direction could be that of using nature-inspired recognition systems, which would allow us to better mimic the subsequent stages of PAS (i.e., SNC part of fig. 1) and to expand the system to model the complete HAS.…”
Section: Discussionmentioning
confidence: 99%
“…Capizzi et al ( 2015 ) showed that particulate matter (PM) is the most dispersed pollutant in major cities. PM concentrations can impact public health and environmental systems and they represent a big concern in urban regions because of their hazards (Aryal et al, 2012 ).…”
Section: Dust Entrainment and Transportmentioning
confidence: 99%
“…• Cascade feed-forward (CFF):is a feed-forward neural network with a direct connection from input to each layer, and from each layer to successive layers [31].…”
Section: B Deep Spatio-temporal Feature Evaluationmentioning
confidence: 99%